Eyelid opening in preterm neonates. Issue 7 (July 1989) - Robinson, J; Moseley, M J; Thompson, J R; Fielder, A R
Abstract : The frequency and patterns of eyelid opening were examined in a group of neonates (gestational age 24-35 weeks). Observations were spread over the 24 hour period to obtain a complete pattern of events. Mean eyelid closure was 74%. When babies were grouped by gestational age, however, differences became apparent, babies of less than 26 weeks having their eyes shut for only 55% of observations compared with 93% at 28 weeks. Trend analysis confirmed that eyelid closure reached a peak at 28 weeks. Neonates exposed to a day/night regimen, opened their eyes significantly more than those exposed to continuous illumination. We suggest that frequency of eyelid opening may be related both to the infant's developmental state (postmenstrual age) and the illumination of the neonatal unit. Frequency of eyelid opening should therefore be considered when calculating the ocular light exposure of preterm neonates.